Analisis Faktor Risiko Tindakan Restrain pada Pasien Rawat Inap dengan Gangguan Jiwa - Jumriani Jumriani; Rini Rachmawaty; Erfina Erfina (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This literature review aims to summarize research results regarding risk factors for restraint in hospitalized mental disorder patients. The literature search used seven databases, namely PuBmed, EBSCOhost, ProQuest, ScienceDirect, Garuda; Google Scholar; and Wiley in the 2013-2023 range. As a result of the research, eleven studies were included in the review, where increased restraint risk factors were divided into three: 1) sociodemographic characteristics (immigrant patients, male, young age, married, rural background, and low socioeconomic); 2) clinical factors (active and aggressive behavior, psychotic/bipolar disorders, cognitive and mood disorders, previous psychiatric disorders, long hospitalization and previous hospitalization, and alcohol/drug dependence); 3) referral factors (forced referrals from emergency departments, from outpatient centers/private doctors, and police referrals). In conclusion, there are three factors that can increase the risk of restraint, namely: sociodemographic characteristics, patient clinical factors, and referral factors. Keywords: Mental Disorder Patients, Hospitalization, Restraint